Analysis of the bacterial community in aged and aging pit mud of Chinese Luzhou‐flavour liquor by combined PCR‐DGGE and quantitative PCR assay. (5th December 2014) - Liang, Huipeng; Li, Wenfang; Luo, Qingchun; Liu, Chaolan; Wu, Zhengyun; Zhang, Wenxue
Abstract BACKGROUND The community structure of bacteria in aged and aging pit mud, which was judged according to their sensory and physicochemical characteristics, was analysed using polymerase chain reaction denaturing gradient gel electrophoresis (PCR‐DGGE) and quantitative real‐time PCR (qPCR). RESULTS The phyla Firmicutes, Actinobacteria, Proteobacteria, Synergistetes and Unclassified Bacteria were detected and the fermentative Firmicutes was predominant in both types of pit mud in the PCR‐DGGE analysis. Among Firmicutes, Clostridiales was dominant in aged pit mud while Bacillales and Lactobacillales were dominant in aging pit mud. The diversity of bacterial communities in aged pit mud was higher than that in aging pit mud. In the qPCR analysis the abundance of Clostridium IV in aged pit mud was higher than that in aging pit mud and there were significant differences in the quantity of Clostridium IV between aged and aging pit mud of the same cellar (P < 0.05). CONCLUSION There were some significant differences in the microbial community structure between aged and aging pit mud. The differences in the quantity of Clostridium IV might be involved in the distinction that the aged pit mud has a strong aroma while the aging pit mud does not. © 2014 Society of Chemical Industry